The Aftermath of Peace: The Impact of the FARC's Ceasefire on Forced Displacement in Colombia - Pedro Albarrán; Antonio Robles; Anna Sanz-de-Galdeano (Institute of Labor Economics (IZA), 2025)
Colombia's prolonged conflict has made the country one of the most affected by forced internal displacement (FID) in the world. This study examines the impact of the FARC's 2014 unilateral and permanent ceasefire on FID. We use a difference-in-differences strategy that exploits the timing of the ceasefire and the pre-conflict distribution of FARC presence across municipalities. Results show a substantial reduction in severe displacement episodes in affected areas, with effects that emerged gradually and persisted over time. These findings highlight the importance of stability and the effective implementation of peace agreements in mitigating FID and its far-reaching consequences.
Keywords: D74; R23; J61; 330; forced internal displacement; armed conflict; ceasefire; FARC; Colombia